2008
DOI: 10.3329/bjp.v4i1.998
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antimicrobial properties of different basil essential oils chemotypes from Togo

Abstract: The aerial parts essential oils of Ocimum basilicum (Lamiaceae) from Togo were steam-distilled and investigated for their percentage composition (GC and GC/ MS) and in vitro antimicrobial activities. Five oil chemotypes were identified and classified as follows in line with their principal components: Estragole type; linalool/estragole type; methyleugenol type; methyleugenol/t-anethole type; tanethole type. The in vitro microbiological experiments revealed that only the methyleugenol and methyleugenol/t-anetho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 19 publications
0
30
0
7
Order By: Relevance
“…The medicinal and aromatic properties of basil are associated with the presence of an essential oil that accumulates in the largest amount in its leaves and flowers. The fresh and dried basil herb is used as an aromatic spice and a source of essential oil, and its main components are also used as plant drugs, since it has antimicrobial (Koba et al 2009) and fungistatic activity (Dambolena et al 2010); moreover, basil oil and its pure components have antimutagenic activity (Stajković et al 2007). Basil oil is a mixture of numerous compounds and its composition is extremely rich and varied.…”
Section: Introductionmentioning
confidence: 99%
“…The medicinal and aromatic properties of basil are associated with the presence of an essential oil that accumulates in the largest amount in its leaves and flowers. The fresh and dried basil herb is used as an aromatic spice and a source of essential oil, and its main components are also used as plant drugs, since it has antimicrobial (Koba et al 2009) and fungistatic activity (Dambolena et al 2010); moreover, basil oil and its pure components have antimutagenic activity (Stajković et al 2007). Basil oil is a mixture of numerous compounds and its composition is extremely rich and varied.…”
Section: Introductionmentioning
confidence: 99%
“…These volatile oils have been applied in perfumery, to inhibit growth of microorganisms, in food preservation and in aromatherapy. The potential uses of O. basilicum, Ocimum canum Ocimum gratissimum and Ocimum sanctum essential oils, particularly as antioxidant and antimicrobial agents have also been explored (Politeo et al, 2007;Koba et al, 2009;Zhang et al, 2009;Hameed et al, 2015c;Altameme et al, 2015b;Hussein et al, 2016a). O. basilicum has been traditionally used for the treatment of many ailments, such as headaches, coughs and diarrhea and it is generally recognized as safe and is a rich source of phenolic antioxidant compounds and flavonoids (Juliani and Simon, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The Sierra Leone O. basilicum examined in the present study was clearly identified as the methyl eugenol chemotype (89.7%). This chemotype had been reported in Togo [19] and Turkey [20]. Methyl eugenol has been known in literature as a powerful insect attractant, [7,[21][22][23], known to attract fruit flies from a distance as far as 0.8 km [7].…”
Section: Resultsmentioning
confidence: 99%